2009
DOI: 10.1007/s00248-009-9490-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Plumage Microbiota Depends on Season and Migration

Abstract: Migratory birds can be efficient dispersers of pathogens, yet we know little about the effect of migration and season on the microbial community in avian plumage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 28 publications
(50 reference statements)
1
26
0
Order By: Relevance
“…Our results showed a strong effect of spatial proximity on bird plumage bacterial community, with birds in closer aviaries showing more similar bacterial communities. In accordance with other studies (Bisson et al , , Saag et al ), they point out the relatively small spatial scale transmission of plumage bacteria. While bacteria are likely transmitted through close contacts (Kulkarni and Heeb ) and reciprocal delousing, some bacteria may be able to survive on non‐feather substrates and, therefore, be transmitted through bathwater, perches, soil and the grids separating the aviaries (Bisson et al ).…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed a strong effect of spatial proximity on bird plumage bacterial community, with birds in closer aviaries showing more similar bacterial communities. In accordance with other studies (Bisson et al , , Saag et al ), they point out the relatively small spatial scale transmission of plumage bacteria. While bacteria are likely transmitted through close contacts (Kulkarni and Heeb ) and reciprocal delousing, some bacteria may be able to survive on non‐feather substrates and, therefore, be transmitted through bathwater, perches, soil and the grids separating the aviaries (Bisson et al ).…”
Section: Discussionsupporting
confidence: 91%
“…Feathers harbour a complex bacterial community that commonly includes feather‐degrading bacteria (Shawkey, Pillai & Hill 2003; Bisson et al. 2007, 2009; Gunderson 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Th is will be most effi cient for bird s living in wetlands and ground-nesting and/or feeding taxa. Although several studies have shown that bird s can transport high numbers of microorganisms (Wuthrich and Matthey, 1980 ;Bisson et al, 2009 ), we are far from having a clear image of the local and global potential dispersal of free-living microorganisms by bird s. A potential limitation of bird s as vectors of free-living microorganisms is that the nesting habitat of many long-distance migratory bird s is very diff erent from their wintering habitats. For example, many shorebirds nest in freshwater wetlands and bogs in the boreal and arctic regions but winter in brackish water wetlands.…”
Section: Potential Factors Governing the Distribution Of Arcellinidamentioning
confidence: 98%